Reverie - La Sala, Ryan (Sourcebooks Fire, 2020)
While recovering from an attack that leaves him without his memory, gay teenager Kane Montgomery stumbles into a world where dreams known as reveries take on a life of their own, and it is up to Kane and a few unlikely allies to stop them before they spillover into the waking world.